2022
DOI: 10.1101/2022.09.08.507157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Death Induced by Survival gene Elimination (DISE) is correlated with neurotoxicity in Alzheimer’s disease and aging

Abstract: Background: Alzheimer's disease (AD) is characterized by progressive neurodegeneration, but the specific events that cause cell death remain poorly understood. Death Induced by Survival gene Elimination (DISE) is a recently discovered powerful cell death mechanism mediated by short (s) RNAs including micro (mi) RNAs acting through the RNA induced silencing complex (RISC). G-rich 6mer seed sequences in the sRNAs (position 2-7) target hundreds of C-rich seed matches in genes essential for cell survival resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 150 publications
2
6
0
Order By: Relevance
“…Our data suggest both an involvement of a v-miRNA as well as a contribution of cellular R-sRNAs to HIV induced cell death. Such a shift of cellular R-sRNAs to more toxic seeds may prime cells for DISE similar to other systems we have tested recently (47, 49).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our data suggest both an involvement of a v-miRNA as well as a contribution of cellular R-sRNAs to HIV induced cell death. Such a shift of cellular R-sRNAs to more toxic seeds may prime cells for DISE similar to other systems we have tested recently (47, 49).…”
Section: Discussionsupporting
confidence: 58%
“…In addition to direct cytotoxic effects of viral RNAs on infected cells, infection with HIV may also shift the ratio of cellular R-sRNAs to more toxic seeds essentially priming the cells to undergo DISE. This effect was recently found in ovarian cancer cells sensitive to chemotherapy compared to treatment resistant cancer cells (47) and in brain cells from Alzheimer’s disease patients compared to normal controls (49).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Both the overall 6mer seed viability of all sequences or differentially expressed sequences can then be determined. We found that small shifts in the 6mer seed viability of Ago bound sRNAs can predict cellular responses to toxic stimuli [14][15][16].…”
Section: Introductionmentioning
confidence: 90%
“…We recently provided evidence to suggest that in a number of models it is the balance of all RISC bound reads with toxic versus nontoxic seeds that can determine cell survival [14][15][16]. Using SPOROS we therefore analyzed the 6mer seed viability of reads that were significantly enriched or depleted (adjusted p-value < 0.05) in the RISC of d.k.o cells infected with the various CD95L mutants.…”
Section: Exploring the Sequence Determinants Of Cd95l Toxicitymentioning
confidence: 99%